2022
DOI: 10.3389/fphar.2021.789570
|View full text |Cite
|
Sign up to set email alerts
|

The Tarantula Venom Peptide Eo1a Binds to the Domain II S3-S4 Extracellular Loop of Voltage-Gated Sodium Channel NaV1.8 to Enhance Activation

Abstract: Venoms from cone snails and arachnids are a rich source of peptide modulators of voltage-gated sodium (NaV) channels, however relatively few venom-derived peptides with activity at the mammalian NaV1.8 subtype have been isolated. Here, we describe the discovery and functional characterisation of β-theraphotoxin-Eo1a, a peptide from the venom of the Tanzanian black and olive baboon tarantula Encyocratella olivacea that modulates NaV1.8. Eo1a is a 37-residue peptide that increases NaV1.8 peak current (EC50 894 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…For example, the scorpion β-toxin BMK I shifts the voltage dependence of both activation and fast inactivation gating to hyperpolarized potentials in rat Na V 1.8, causing an increase in small diameter DRG TTX-R Na + current and pain-related behavior ( Ye et al, 2015 ). Similarly, the recently described tarantula toxin β-theraphotoxin-Eo1a activates Na V 1.8 and causes pain in house mice by hyperpolarizing activation and steady-state fast inactivation ( Deuis et al, 2021 ). The DIV voltage-sensor-binding toxins Hm1a and LqqIV shift the voltage dependence of Na V 1.1 fast inactivation gating to depolarized potentials, increasing channel availability and window currents ( Osteen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the scorpion β-toxin BMK I shifts the voltage dependence of both activation and fast inactivation gating to hyperpolarized potentials in rat Na V 1.8, causing an increase in small diameter DRG TTX-R Na + current and pain-related behavior ( Ye et al, 2015 ). Similarly, the recently described tarantula toxin β-theraphotoxin-Eo1a activates Na V 1.8 and causes pain in house mice by hyperpolarizing activation and steady-state fast inactivation ( Deuis et al, 2021 ). The DIV voltage-sensor-binding toxins Hm1a and LqqIV shift the voltage dependence of Na V 1.1 fast inactivation gating to depolarized potentials, increasing channel availability and window currents ( Osteen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms that regulate Na V 1.8 gating are not completely understood. While animal-derived toxins have provided tools for examining structure-activity relationships in several Na V , fewer toxins have been identified that modify Na V 1.8 gating ( Ye et al, 2015 ; Zhang et al, 2019 ; Deuis et al, 2021 ). AZ bark scorpions produce venoms rich in peptide toxins that modify the gating mechanisms of Na + ion channels in nerve and muscle tissue ( Jaimovich et al, 1982 ; Couraud et al, 1984 ; Possani et al, 1999 ; Corona et al, 2001 ; Rodríguez de la Vega and Possani, 2005 ; Carcamo-Noriega et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…97 Another example is b-theraphotoxin-Eo1a, a 37-amino acid residue ICK peptide from the Tanzanian black and olive baboon tarantula, Encyocratella olivacea, that selectively activates Na V 1.8 (EC 50 894 nM) by binding to the DII S3-S4 loop. 31 Although the role of Na V 1.8 in pain signalling is well established, relatively few modulators of Na V 1.8 have been described. Despite being an activator, Eo1a provides important structure-activity data that may be used for the rationale design of selective Na V 1.8 inhibitors.…”
Section: Spidersmentioning
confidence: 99%